Promoting Positive Behaviours using Sociodrama - Deanna McLennan; Kara Smith (University of Windsor, 2007)
This study investigates whether the use of sociodramatic activities created by Augusto Boal can promote self-expression, a commitment to learning, and positive behaviour in grade eight students. Twenty-four 'at-risk' students were identified by the school principal, and participated in 10 weekly 45-minute drama sessions. Initially, participants exhibited behavioural problems such as a lack of motivation, multiple social problems, and a demonstrated lack of respect toward peers and teaching staff. Data from the sessions were collected through participant journals, field notes, questionnaires and member checks. Gender differences were observed in participation levels during activities and discussions. Student responses indicated that the use of sociodramatic techniques provided multiple opportunities for self-expression. Most girls in the study were involved in the dramatic activities and discussions on a consistent basis from the beginning, whereas most boys were inactive participants at the beginning, but increased their commitment, and even assumed leadership roles by the conclusion. While changes in self-expression and commitment to learning may have been the result of students engaging in routinely scheduled drama activities, the study found that sociodrama activities based on Boal, when implemented in the classroom, might have the potential to encourage positive behaviour in at-risk students.